Workshop civil society participation in a new EU-ACP partnership. - INZET Association (Amsterdam : INZET Association, 1999)
Documentatie bestaat uit:- Civil society participation in a new EU-ACP partnership : report of a workshop - text: Bram Posthumus, editing: Margriet Kuster- The process of renegotiating the lomé convention : The place and the involvement of civil society : background paper for the workshop civil society participation in a new EU-ACP partnership - by Youssouf Cissé ; translated from French by Peter Mason- Civil society, development and lomé : policiy options for EU-ACP relations - by: George Huggins
Engels
Brochure
Keywords: burgerparticipatie